근로자 참여가 노동조합에 미치는 영향: 탐색적 연구 - 김동배(Dong-Bae Kim); 박경원(Kyoung-Won Park) (대한경영학회지, 2014)
본 연구는 한국노동연구원의 사업체패널 자료를 사용하여 근로자 참여가 노동조합에 미치는 영향을 분석하였다. 근로자 참여는 작업장수준 참여와 노사협의회의 활성화 등 7가지 관행의 합산지수로 측정하였다. 고정효과모형에 의한 추정 결과 근로자 참여는 노동조합 조직률과 비선형(∩형)의 관계가 나타났으며,이러한 관계는 근로자 참여의 측정 방식을 달리해도 일관되게 나타났다. 이상의 분석결과는 근로자 참여와 노동조합 간 부(-)의 관계를 발견한 미국의 선행연구와 다르고, 근로자 참여와 노동조합 간 대체로 정(+)의 관계를 발견한 미국 이외 국가들의 선행연구와도 다르다. 이상의 분석결과가 갖는 함의를 요약하고,추후 연구 과제를 제시하였다. This study examines the effect of employee involvement on the labor union, using the KoreaLabor Institute's 2005-2011 Workplace Panel Survey. Specifically, it focuses on how the index ofemployee involvement, measured by the degree of which suggestion program, small groupactivity, job rotation, multi-skilling, regular team meeting, communication, and works council areutilized at the establishments, affects union density. The empirical results based on the fixedeffect model suggest that employee involvement has an inverted U relationship with uniondensity. The results are found to be consistent with the use of an index of employee involvementmeasured by whether each of the programs is adopted or not. While the results confirms that theeffect of employee involvement on labor union depends on the quality of industrial relations, theyare different from those of the previous studies that show a linear (either negative or positive)relationship between employee involvement and labor union. The authors discuss the implicationsof the empirical findings. KCI Citation Count: 5